Identification of genetic risk loci for depression and migraine comorbidity in Han Chinese residing in Taiwan - Tsai, Ming-Chen; Tsai, Chia-Lin; Liang, Chih-Sung; Lin, Yu-Kai; Lin, Guan-Yu; Tsai, Chia-Kuang; Yeh, Po-Kuan; Liu, Yi; Hung, Kuo-Sheng; Yang, Fu-Chi (Frontiers in Psychiatry, 2023)
The genetic association between depression and migraine has not been well investigated in Asian populations. Furthermore, the genetic basis of depression and comorbid migraine subtypes remains nebulous. Hence, in the current study we investigate the susceptibility loci associated with depression and migraine comorbidity in the Han Chinese population in Taiwan. More specifically, we perform a genome-wide association study involving 966 migraine patients, with or without comorbid depression. Genotyping is performed using participant genomic DNA. Association analyses are performed for the entire migraine cohort (subgroups: episodic migraine, chronic migraine, and migraine with or without aura). Results show that the single nucleotide polymorphism variants of the CDH4 intron region (rs78063755), NTRK3-AS1 downstream region (rs57729223), and between LINC01918 and GPR45 (rs2679891) are suggestively associated with depression. Twenty additional susceptibility loci occur within the subgroups. A multivariate association study demonstrated that a variant in the intron region of CDH4 rs78063755 was associated with Beck Depression Inventory and Migraine Disability Assessment scores. The findings of this study identify several genetic loci suggestively associated with depression among migraine patients in the Han Chinese population. Moreover, a potential genetic basis has been characterized for depression and migraine comorbidity, thus providing genetic candidates for further investigation.